Some data on health condition of the students of Vilnius Teachers‘ Training Institute (On the basis of the data of 1967-1971) - Ragalevičius , L.; Leimonienė , R. (Psichologija, 1972)
The prophylaxis and treatment of students is carried on by the Clinics of higher schools. It can be stated that the students’ health condition has improved of late, but for eyesight troubles. Besides, the number of students appointed for special physical training has also increased.